2015
DOI: 10.1016/j.bbamem.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Membrane accessibility of glutathione

Abstract: Regulation of the ion pumping activity of the Na+,K+-ATPase is crucial to the survival of animal cells. Recent evidence has suggested that the activity of the enzyme could be controlled by glutathionylation of cysteine residue 45 of the β-subunit. Crystal structures so far available indicate that this cysteine is in a transmembrane domain of the protein. Here we have analysed via fluorescence and NMR spectroscopy as well as molecular dynamics simulations whether glutathione is able to penetrate into the interi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Furthermore, the increases in carboxylates caused by the GSH treatment also suggest that additional mechanisms may occur. On the other hand, the pathway of GSH entrance in leaves has not been studied so far, but the fact that GSH is unable to penetrate lipid membranes ( Garcia et al., ) suggests that the entrance is likely to be via stomata, as it occurs with molecules of similar size [the molecular weight of GSH and Fe(III)‐EDDHA is ca. 307 and 435, respectively] ( Rios et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the increases in carboxylates caused by the GSH treatment also suggest that additional mechanisms may occur. On the other hand, the pathway of GSH entrance in leaves has not been studied so far, but the fact that GSH is unable to penetrate lipid membranes ( Garcia et al., ) suggests that the entrance is likely to be via stomata, as it occurs with molecules of similar size [the molecular weight of GSH and Fe(III)‐EDDHA is ca. 307 and 435, respectively] ( Rios et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown that the E1 state of the enzyme favors the cysteine to be glutathionylated more than the E2 state (Garcia et al, 2015). …”
Section: Betasmentioning
confidence: 99%
“…Furthermore, exposure to the antioxidant glutathione, which is critical for neuronal protection against ROS 102 , only attenuated L-DOPA-induced parkin loss by half. Although glutathione lacks membrane permeability 103,104 and does not react efficiently with all kinds of ROS 105 , glutathione treatment has been previously shown to be effective at completely preventing the autoxidation of both L-DOPA and the dopamine analog 6-hydroxydopamine (6-OHDA) to their respective quinones 106,107 . Additionally, glutathione treatment has been found to completely prevent cell death induced by L-DOPA 106 , 6-OHDA 107 , dopamine 108110 , hydrogen peroxide 107 , and the oxidant nitric oxide 111 .…”
Section: Discussionmentioning
confidence: 99%